Calculation of Asynchronous Motor Characteristics using Electronic Computer - V. V. Romanov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers calculation method for operational, U-type and angular characteristics of asynchronous motor using personal computer. This method is based on its vector diagram. The paper contains algorithms, block diagram and calculations of characteristics of a concrete asynchronous motor which practically do not differ from the results obtained on the basis of well-known calculative methods.